Collaborating, Learning, and Adapting Framework & Key Concepts (USAID)
Although collaborating, learning, and adapting (CLA) are not new to USAID, they often do not happen regularly or systematically and are not intentionally resourced. The CLA framework above identifies components and subcomponents to help you think more deliberately about what approach to CLA might be best tailored to your organizational or project context. The framework recognizes the diversity of what CLA can look like in various organizations and projects while also giving CLA structure, clarity, and coherence across two key dimensions: CLA in the Program Cycle: how CLA is incorporated throughout Program Cycle processes, including strategy, project, and activity design and implementation; and Enabling Conditions: how an organization’s culture, business processes, and resource allocation support CLA integration. Organizations need both integrated CLA practices appropriate for their context and conducive enabling conditions to become stronger learning organizations capable of managing adaptively. The framework stresses the holistic and integrated nature of the various components of CLA to reinforce the principle that CLA is not a separate workstream—it should be integrated into existing processes to strengthen the discipline of development and improve aid effectiveness.